The Relationship of Knowledge and Perception with Mental Health in Housewives During the COVID-19 Pandemic in Cot Ba'u Village, Sukajaya Sabang District, 2021 - Miftahul Jannah; Agustina Agustina (Universitas Serambi Mekkah, 2022)
Mental health is a state of well-being in which a person realizes his abilities, is able to cope with problems, pressures and is able to work productively, and can contribute to society. In Indonesia, there are several regions experiencing psychological problems related to the COVID-19 pandemic, one of which is Aceh as much as 1.6%. Psychological problems faced such as anxiety as much as 63%, 66% of depression, and 64.3% of psychological trauma.This research was a descriptive analytic study with a cross sectional design. The populations in this study were housewives in Gampong Cot Ba'u, Sukajaya Sabang District, amounting to 95 people. Sampling was done by proportional random sampling technique. Data analysis used univariate and bivariate analysis, with chi-square statistical test. Data collection was carried out from July 30 to August 8, 2021. The results showed that housewives with mental health disorders (8.45%), mothers with good knowledge (95,8%) and mothers with positive perceptions (92.6%). Bivariate analysis showed that there was no relationship between knowledge (0.222), and perception (0.405) with the mental health of housewives during the COVID-19 pandemic. So that, there was no relationship between knowledge and perception with the mental health of housewives in Gampong Cot Ba'u, Sukajaya Sabang District in 2021. It is recommended for housewives to maintain physical and mental health during the COVID-19 pandemic. Keywords: mental health, knowledge, perception, COVID-19.